2018
DOI: 10.1159/000489917
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Factor KDM2B Regulates EMT and Small GTPases in Colon Tumor Cells

Abstract: Background/Aims: The epigenetic factor KDM2B is a histone demethylase expressed in various tumors. Recently, we have shown that KDM2B regulates actin cytoskeleton organization, small Rho GTPases signaling, cell-cell adhesion and migration of prostate tumor cells. In the present study, we addressed its role in regulating EMT and small GTPases expression in colon tumor cells. Methods: We used RT-PCR for the transcriptional analysis of various genes, Western blotting for the assessment of protein expression and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…Evident from Fan et al corroborated that KDM2B accelerated cell proliferation in triple‐negative breast cancer cells via repression of p15 INK4B , p16 INK4A , and p57 KIP2 transcription (Zheng et al, ). Otherwise, KDM2B was also proven to mediate epithelial‐mesenchymal transition process and small GTPases in colon cancer cells (Zacharopoulou, Tsapara, Kallergi, Schmid, Alkahtani, et al, ). In the actual research, we attempted to uncover whether KDM2B acetylation triggered by CBP could affect the carcinogenesis of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evident from Fan et al corroborated that KDM2B accelerated cell proliferation in triple‐negative breast cancer cells via repression of p15 INK4B , p16 INK4A , and p57 KIP2 transcription (Zheng et al, ). Otherwise, KDM2B was also proven to mediate epithelial‐mesenchymal transition process and small GTPases in colon cancer cells (Zacharopoulou, Tsapara, Kallergi, Schmid, Alkahtani, et al, ). In the actual research, we attempted to uncover whether KDM2B acetylation triggered by CBP could affect the carcinogenesis of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, KDM2B was also proven to mediate epithelial-mesenchymal transition process and small GTPases in colon cancer cells (Zacharopoulou, Tsapara, Kallergi, Schmid, Alkahtani, et al, 2018). In the actual research, we attempted to uncover whether KDM2B acetylation triggered by CBP could affect the carcinogenesis of colon…”
Section: Discussionmentioning
confidence: 99%
“…KDM2B functions as an oncogene in several types of tumors. Following the original discovery of its oncogenic potential in Moloney murine leukemia virus (MoMuLV)-induced rodent T cell lymphomas, where it was found to be activated by provirus integration Tzatsos et al, 2009), it has been shown to function as an oncogene in human lymphoid (Andricovich et al, 2016) and myeloid malignancies (van den Boom et al, 2016) as well as in bladder cancer (Kottakis et al, 2011) (McNiel andTsichlis, 2017) and pancreatic cancer (Tzatsos et al, 2013), basal-like breast cancer (Kottakis et al, 2014), gliomas (Wang et al, 2018) and prostate cancer (Zacharopoulou et al, 2018). The oncogenic potential of KDM2B is mediated by multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Induction of the EMT promotes cell invasion, migration, and metastasis, which confers stem-celllike characteristics on cancer cells, and induces therapeutic resistance. 37,38 Cellular signaling responses to hypoxia and inflammation involve crosstalk through upregulation of HIF-1α and associated tumorigenic activities, which are mediated by the inflammatory cytokine interferon-α. In addition, expression of HIF-1α is related to EMT.…”
Section: Discussionmentioning
confidence: 99%